2006
DOI: 10.1116/1.2192530
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-plasma assisted molecular beam epitaxial growth of high-purity InAs

Abstract: Articles you may be interested inMolecular beam epitaxy growth of high electron mobility InAs/AlSb deep quantum well structure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The electron concentration in InAs NW is as suggested nonuniform . The concentration of the inner NW is close to that of bulk InAs, and at the level of 10 15 –10 16 cm –3 , whereas that at the NW surface is ∼10 18 cm –3 . , The inset in Figure a shows the estimated SCR length x in the NW side against effective donor concentration in NW with the effective acceptor concentration in the substrate to be 5 × 10 16 cm –3 . The x is 1000–400 nm for N D = 10 15 –10 16 cm –3 whereas it is negligible for N D = 10 18 cm –3 , indicating that the built-in electric field hardly affects the carriers at the NW surface.…”
mentioning
confidence: 57%
“…The electron concentration in InAs NW is as suggested nonuniform . The concentration of the inner NW is close to that of bulk InAs, and at the level of 10 15 –10 16 cm –3 , whereas that at the NW surface is ∼10 18 cm –3 . , The inset in Figure a shows the estimated SCR length x in the NW side against effective donor concentration in NW with the effective acceptor concentration in the substrate to be 5 × 10 16 cm –3 . The x is 1000–400 nm for N D = 10 15 –10 16 cm –3 whereas it is negligible for N D = 10 18 cm –3 , indicating that the built-in electric field hardly affects the carriers at the NW surface.…”
mentioning
confidence: 57%
“…Hydrogen has also been reported to passivate defects in bulk and quantum well materials [2] and, recently, the quantum dot structures [3]. It is also reported that continuous irradiation by atomic hydrogen during epitaxial growth is more efficient for passivation of misfit dislocations than after growth H-plasma treatment [4][5][6]. However, for most of the cases the improvement drops after thermal treatment above around 300 • C due to the escape of hydrogen at elevated temperature.…”
Section: Many Device Applications Of Nanostructures Includingmentioning
confidence: 99%
“…Atomic-H has proved to be effective in passivating carrier concentration and improving material purity in III-V materials such as GaAs and InAs [6][7][8][9][10]. Furthermore, it has been found that atomic-H helps to promote an ideal layer-by-layer two-dimensional nucleation and step-flow growth mode on GaAs (100) substrate at low growth temperatures, thereby resulting in atomically flat surfaces [9].…”
Section: Introductionmentioning
confidence: 98%